3,3′-Diallyl-1,1′-[o-phenylenebis(methylene)]diimidazol-3-ium bis(hexafluorophosphate) - Haque, Rosenani A. (International Union of Crystallography, 2011)
In the cation of the title molecular salt, C(20)H(24)N(4) (2+)·2PF(6) (−), the central benzene ring makes dihedral angles of 84.19 (7) and 79.10 (7)° with the pendant imidazole rings. In one of the hexafluorophosphate anions, the six F atoms are disordered over two sets of sites, with an occupancy ratio of 0.842 (3):0.158 (3). In the crystal, the cations and anions are linked by numerous C—H⋯F hydrogen bonds, thereby forming a three-dimensional network.